PROBLEMATIKA PEMBERIAN STATUS JUSTICE COLLABORATOR KEPADA PELAKU TINDAK PIDANA KORUPSI OLEH APARAT PENEGAK HUKUM - Anastacia Esteliana Mailoor (2022)
Granting Justice Collaborator status to perpetrators of corruption crimes is one of the strategy that law enforcement officers can use in disclosing corruption cases. In determining that it must meet the requirements that apply in the legislation, However, in practice, there is still a perpetrator who has committed a corruption and has not met the regulated requirements about Justice Collaborators. In addition, the role and authority of law enforcement officers in collaborating is also needed to determine a justice collaborator. However, the coordination between the apparatuses is still lacking. This study uses the theory of legal certainty and the theory of law enforcement in analyzing the existing problems due to unclear certainty in terms of applying the requirements that apply in the legislation and the lack of cooperation between law enforcement officers, which is related to law enforcement itself. Then also disscused with the concepth of an integrated criminal justice system. This study uses a normative juridical method that examines several regulations regarding justice collaborators, such as the Law on the Protection of Witnesses and Victims, the Circular Letter of the Supreme Court Number 4 of 2011, and Joint Regulations by Law Enforcement Officials. This research also uses a statutory approach, a case approach, and conceptual approach. In this study, the discussion includes various perspectives from law enforcement officers to determine justice collaborator, while in terms of coordination and cooperation with law enforcement officers, it is discussed in terms of the criminal justice process in Indonesia. Keywords: Justice Collaborator, Corruption Crimes, Law Enforcement Officers